Chitosan impregnated sugarcane bagasse biochar for removal of anionic dyes from wastewater - Magda A. Akl; Asmaa A. Serage (Scientific Reports)
Abstract Wastewater treatment is of utmost importance in providing all equitable and safe drinking water. In the present study, a chitosan impregnated sugarcane bagasse biochar SCNC biocomposite has been synthesized for the removal of Congo red (CR) dye from an aqueous solution. The SCNC biocomposite was thoroughly characterized through Brunauer, Emmett and Teller (BET) and N2 adsorption isotherm, point of zero charge (pHPZC), elemental analysis, Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and Thermogravimetric analysis (TGA) analysis. Moreover, SCNC biocomposite was further employed to remove CR dye from the aqueous solution in batch mode. The SCNC biocomposite could remove more than 95.0% of CR at an initial concentration of (100mgL− 1), adsorbent dosage (0.05 g), time (200 min), pH ~ 3. The SCNC biocomposite achieved maximum adsorption capacity of 170mgg− 1. The equilibrium adsorption data for CR dye were best fitted to the Langmuir isotherm model with R2, 0.999. The kinetic and isotherm were statistically investigated using the chi-square statistic (χ2 ), mean square error (MSE), and the sum of squares error (SSE) Because of the higher correlation coefficient (R2 ≥ 0.999) and lower error functions, the equilibrium CR adsorption isotherms for a single-dye system fit Langmuir and the PSO kinetic model. The thermodynamic studies revealed the spontaneous and endothermic nature of adsorption of CR dye onto SCNC biocomposite. The SCNC biocomposite can be regenerated up to the 5th cycle successfully. The mechanism of CR adsorption onto SCNC was elucidated.